Rapid-onset clinical and mechanistic effects of anti-C5aR treatment in the mouse collagen-induced arthritis model. (9th June 2014) - Andersson, C; Wenander, C S; Usher, P A; Hebsgaard, J B; Sondergaard, B-C; Rønø, B; Mackay, C; Friedrichsen, B; Chang, C; Tang, R; Hornum, L
Summary: Preclinical evidence supports targeting the C5a receptor (C5aR) in rheumatoid arthritis (RA). To support ongoing clinical development of an anti-C5aR monoclonal antibody, we have investigated for the first time the mechanism of action and the pharmacodynamics of a blocking anti-murine C5aR (anti-mC5aR) surrogate antibody in mouse collagen-induced arthritis (CIA). First, efficacy was demonstrated in a multiple-dose treatment study. Almost complete inhibition of clinical disease progression was obtained, including reduced bone and cartilage destruction in anti-mC5aR-treated mice. Then, the mechanism of action was examined by looking for early effects of anti-mC5aR treatment in single-dose treatment studies. We found that 48 h after single-dose treatment with anti-mC5aR, the neutrophil and macrophage infiltration into the paws was already reduced. In addition, several inflammatory markers, including tumour necrosis factor (TNF)-α, interleukin (IL)-6 and IL-17A were reduced locally in the paws, indicating reduction of local inflammation. Furthermore, dose-setting experiments supported a beneficial clinical effect of dosing above the C5aR saturation level. In conclusion, these preclinical data demonstrated rapid onset effects of antibody blockade of C5aR. The data have translational value in supporting the Novo Nordisk clinical trials of an anti-C5aR antibody in rheumatoid arthritis patients, by identifying potential biomarkers of treatment effects as well as by providing information on pharmacodynamics and novel insights into the mechanism of action of monoclonal antibody blockade of C5aR.